2018 IEEE 59th Annual Symposium on Foundations of Computer Science (FOCS) 2018
DOI: 10.1109/focs.2018.00016
|View full text |Cite
|
Sign up to set email alerts
|

Hardness Magnification for Natural Problems

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 50 publications
2
44
0
Order By: Relevance
“…Most recently, the reference [19] proves Theorem 1.3 for deterministic formula lower bounds of size n 3+ε ; we generalize their results for probabilistic formula lower bounds of size n 2+ε . Our Theorem 1.5 generalizes n 2−ε -size formula lower bounds for MCSP [32,54,55] on larger circuit sizes. In [19,54,55] it is shown that an n 3+ε -size formula lower bound for MKtP[n o (1) ] implies EXP NC 1 , and [32,54] showed that MKtP[polylog(n)] does not have n 2−ε -size formulas.…”
Section: Theorem 15 (Sub-quadratic Mktp and Mcsp Lower Bounds)mentioning
confidence: 66%
See 2 more Smart Citations
“…Most recently, the reference [19] proves Theorem 1.3 for deterministic formula lower bounds of size n 3+ε ; we generalize their results for probabilistic formula lower bounds of size n 2+ε . Our Theorem 1.5 generalizes n 2−ε -size formula lower bounds for MCSP [32,54,55] on larger circuit sizes. In [19,54,55] it is shown that an n 3+ε -size formula lower bound for MKtP[n o (1) ] implies EXP NC 1 , and [32,54] showed that MKtP[polylog(n)] does not have n 2−ε -size formulas.…”
Section: Theorem 15 (Sub-quadratic Mktp and Mcsp Lower Bounds)mentioning
confidence: 66%
“…Our Theorem 1.5 generalizes n 2−ε -size formula lower bounds for MCSP [32,54,55] on larger circuit sizes. In [19,54,55] it is shown that an n 3+ε -size formula lower bound for MKtP[n o (1) ] implies EXP NC 1 , and [32,54] showed that MKtP[polylog(n)] does not have n 2−ε -size formulas. That is, the "gap" between the magnification threshold and known lower bounds was n 3+ε versus n 2−ε .…”
Section: Theorem 15 (Sub-quadratic Mktp and Mcsp Lower Bounds)mentioning
confidence: 66%
See 1 more Smart Citation
“…It is important to note, in this regard, that lower bounds have been proved for MCSP that essentially match the strongest lower bounds that we have for any problems in NP [16]. There is now a significant body of work, showing that slight improvements to those bounds, or other seemingly-attainable lower bounds for GapMKtP or GapMCSP or related problems, would yield dramatic complexity class separations [12][13][14][15]34,38,39,45].…”
Section: Magnificationmentioning
confidence: 65%
“…A recent line of research on hardness magnification[16,14] provides another motivation for proving relatively weak lower bounds for restricted circuit models against certain "gap variants" of MCSP. Such lower bounds are shown to imply much stronger (superpolynomial) lower bounds.…”
mentioning
confidence: 99%